METTL3-mediated m6A modification of has_circ_0007905 promotes age-related cataract progression through miR-6749-3p/EIF4EBP1 - Rui Li; Haohao Zhu; Qian Li; Jiancen Tang; Yiping Jin; Hongping Cui (PeerJ, 2023)
Many cases of blindness are caused by age-related cataracts (ARCs). N6-methyladenosine (m6A)-modified circRNA widely participates in disease progression. However, the role of m6A modification of circRNA in ARC is unclear. We mined and elucidated the functions and mechanisms of key circRNAs with m6A modification involved in ARC progression. The GSE153722 dataset was used to mine m6A-mediated key circRNA. Loss-of-function assays and rescue assays were used to explore the effect and mechanism of circRNA on ARC cell proliferation and apoptosis. Has_circ_0007905 was a hypermethylated and upregulated expression in the ARC group relative to the control group both in vivo and in vitro. Silencing of has_circ_0007905 promoted proliferation and inhibited the apoptosis of HLE-B3 cells. METTL3 was upregulated in HLE-B3 cells after ARC modeling and had four binding sites with has_circ_0007905 and a mediated m6A modification of has_circ_0007905. Proliferation was significantly inhibited and apoptosis of HLE-B3 cells was facilitated by METTL3 overexpression, whereas these effects were prevented by has_circ_0007905 silencing. Silencing of has_circ_0007905 led to an alteration in the transcriptome landscape. Differentially expressed genes were mainly involved in immune-related processes and pathways. EIF4EBP1 overexpression promoted apoptosis and suppressed proliferation, and also significantly reversed effects of has_circ_0007905 silencing. Moreover, miR-6749-3p significantly decreased the luciferase activities of wild type plasmids with both of has_circ_0007905 and EIF4EBP1. MiR-6749-3p inhibitor blocked elevation in proliferation and reduced EIF4EBP1 expression and apoptosis conferred by has_circ_0007905 silencing. We reveal for the first time that the commitment of ARC progression is guided by METTL3/has_circ_0007905/miR-6749-3p/EIF4EBP1 axis, and the results provide new insights into ARC pathology.